Tempus fugit, the baroque fugue to face the contemporary time crisis - Cabrera Torrecilla, Angélica (Res Publica. Revista de Historia de las Ideas Políticas, 2023)
This article proposes a comparative research study on the idea of fugue developed at the Baroque period, as a critical tool for facing the contemporary temporal crisis provoked by an accelerationist hegemony. The aim is to demonstrate that, symbolically, the fugue allows a comparative analysis between contemporary and Baroque temporalities, since in both the fugue refers to change and transience. However, while in the former fugue is linked to a prospective time framed in acceleration and hyper-consumption; in the Baroque, fugue enhances the moment, making inflection and conjuncture possible. Thus, the fugue is analyzed as a temporal allegory in the intellectual and cultural production of the Baroque. From the notions and uses of movement, counterpoint, rhetoric and folding, the baroque fugue provides us with a polysemic significance capable of extending the current constrictions on temporal transience.
Keywords: Fugue; Transience; Crisis; Time; Accelerationism